Simulation of Coastal Erosion Model to Support Disaster Mitigation in Coastal Sayung, Demak District - Ahsan Habib; Suripin Suripin; Denny Nugroho Sugianto (International Conference on Coastal and Delta Areas, 2017)
Coastal Sayung, Demak has occurred agricultural land and mangroves conversion for opening the ponds. Land use change inflict 2 small villages sink, namely Tambaksari (1997) and Rejosari (2004). The small villages are damaged by coastal erosion. This coast is an area affected by tides. The study aims to evaluate the erosion in coastal Sayung, by simulation model with mathematic model. The simulation results are calibrated with March and June 2016 bathymetry data. Bathymetry data is obtained by echosounder to acquiring contour depth. Wind data was obtained from NOAA for 10 years. Sediment sampling results indicate the type of silt (72%), clay (24%), and fine sand (4%), with specific gravity 1.51 – 1.85 tons/m3. The data used for hydrodynamics and erosion modeling with mathematic model. The simulation results indicate the greatest erosion value occurs in the transition season I, which is 94,000 m3. Patterns of erosion strongly influenced by the current patterns of a particular season. When the West, current and erosion patterns move towards northeast, and otherwise with the East. The most eroded villages are Sriwulan and Bedono, then Timbulsloko, and the smallest is Surodadi. The results of this study can be used to support disaster mitigation in the coastal Sayung, Demak. Keywords: bathymetry, coastal Sayung, erosion, mathematic model, sediment